Stereotypes, emotions, and behaviors associated with animals: A causal test of the stereotype content model and BIAS map. (September 2019) - Sevillano, Verónica; Fiske, Susan T.
Using the stereotype content model (SCM; Fiske, Cuddy, Glick, & Xu, 2002) and the behaviors from intergroup affect and stereotypes (BIAS) map (Cuddy, Fiske, & Glick, 2007), two experiments tested the effect of animal stereotypes on emotions and behavioral tendencies toward animals. As a novel approach, Study 1 ( N = 165) manipulated warmth and competence traits of a fictitious animal species ("wallons") and tested their effect on emotions and behaviors toward those animals. Stereotypical warm-competent and cold-incompetent "wallons" elicited fondness/delight and contempt/disgust, respectively. Cold-competent "wallons" primarily elicited threat but not awe. Warm-incompetent "wallons" were elusive targets, not eliciting specific emotions. The warmth dimension determined active behaviors, promoting facilitation (support/help) and reducing harm (kill/trap). The competence dimension determined passive behaviors, eliciting facilitation (conserve/monitor) and reducing harm (ignore/let them die off). Study 2 ( N = 112) tested the relation between animal stereotypes for 25 species and realistic scenarios concerning behavioral tendencies toward animals. Similar to Study 1, stereotypically warm (vs. cold) animals matched with active scenarios, eliciting more facilitation (i.e., national health campaign) but less harm (i.e., fighting animals). Stereotypically competent (vs. incompetent) animals matched with passive scenarios, eliciting more facilitation (i.e., restricted areas) but less harm (i.e., accidental mortality). Accordingly, stereotypes limited the suitability of scenarios toward animals. Although findings are consistent with the SCM/BIAS map framework, several unpredicted results emerged. The mixed support is discussed in detail, along with the implications of an intergroup approach to animals.